2016
DOI: 10.7863/ultra.16.01097
|View full text |Cite
|
Sign up to set email alerts
|

Nonobstructive Diffuse Dilated Bowel Loops: Prenatal Diagnosis, Fetal Characteristics and Neonatal Outcomes

Abstract: Nonobstructive diffuse dilated bowel loops diagnosed in the second half of pregnancy are associated with premature rupture of membranes and premature labor. As neonatal gastrointestinal complications may be anticipated, prenatal parental counseling with a neonatologist and pediatric gastroenterologist should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Congenital diarrhea was observed at birth in four of the five cases, for which appropriate postnatal care is necessary 28,29 . However, as previously observed by Katz et al 9 . and Amino et al., 30 this typical prenatal appearance was observed in one of our cases in which the infant presented no anomaly at birth.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Congenital diarrhea was observed at birth in four of the five cases, for which appropriate postnatal care is necessary 28,29 . However, as previously observed by Katz et al 9 . and Amino et al., 30 this typical prenatal appearance was observed in one of our cases in which the infant presented no anomaly at birth.…”
Section: Discussionsupporting
confidence: 78%
“…Congenital diarrhea was observed at birth in four of the five cases, for which appropriate postnatal care is necessary. 28,29 However, as previously observed by Katz et al 9 and Amino et al, 30 this typical prenatal appearance was observed in one of our cases in which the infant presented no anomaly at birth. Because drainage of amniotic fluid is needed in most cases, this can be the opportunity to perform a biochemical analysis of digestive enzymes and electrolytes in the amniotic fluid and a genetic analysis to confirm the diagnosis.…”
Section: Prenatal Magnetic Resonance Imagingsupporting
confidence: 87%
See 2 more Smart Citations
“…The differential diagnosis of etiologies underlying the relatively infrequent third-trimester sonographic depiction of dilated fetal bowel includes (functional or mechanical) bowel obstruction, intestinal atresia, volvulus, annular pancreas, intestinal malrotation, intussusception, gastrointestinal duplications, cystic fibrosis-associated meconium ileus, congenital chloride diarrhea, microvillus inclusion disease, intestinal neuronal dysplasia, and meconium plug syndrome [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] . Fetal bowel obstruction may be associated with aneuploidy (mostly Trisomy 21 in association with esophageal or duodenal atresia), and rarely select microduplications or deletions, with a detection rate in cases of low risk of aneuploidy of 3.85% by copy number variation sequencing (CNV-seq) in contrast to 7.69% by whole exome sequencing (WES) [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%